Ten-year cardiovascular risk in patients with stable angina pectoris but without coronary artery disease by coronary angiography. (25th November 2020) - Olesen, K.K.W; Botker, H.E; Sorensen, H.T; Maeng, M
Abstract: Background: Patients with stable angina pectoris who do not have obstructive coronary artery disease (CAD) by coronary angiography are presumed to have a continued high cardiovascular risk despite no CAD. Purpose: We examined the 10-year risk of myocardial infarction (MI), major adverse cardiovascular events (MACE), and death in elective patients with stable angina pectoris, but without CAD by coronary angiography compared to an age and sex matched general population cohort from Western Denmark. Methods: We performed a cohort study of patients with stable angina pectoris without obstructive CAD by elective CAG examined between 2003 and 2016 in Western Denmark. Patients were compared to an age and sex matched general population comparison cohort without previous MI or coronary revascularization. Outcomes were MI, MACE (a composite of MI, ischemic stroke, and cardiac death), and death. Maximum follow-up was 10 years. Adjusted incidence rate ratios (IRRs) were computed using conditional Poisson regression. We also did a stratified analysis by sex and levels of comorbidity. Results: A total of 18, 491 patients suspected of angina pectoris without obstructive CAD, and 92, 387 individuals from the general population were included in the study. Median follow-up was 8.6 years. Patients with chest pain but without CAD had reduced risk of MI (adjusted IRR 0.59, 95% CI 0.50–0.70, Figure), MACE (adjusted IRR 0.64, 95% CI 0.57–0.80), and death (adjusted IRR 0.62, 95% CI 0.59–0.67) compared to the general population when adjusting for potential confounders. Results were consistent when stratifying by sex and levels of comorbidity. Conclusions: Absence of angiographic obstructive CAD in patients with symptoms of stable angina pectoris was associated with favorable low 10-year cardiovascular risk and mortality compared to the general population without known coronary status. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): Department of Cardiology, Aarhus University Hospital